Corruption: Expanding the Focus - Barcham, Manuhuia; Hindess, Barry; Larmour, Peter (ANU Press, 2012)
Recent years have seen an unprecedented rise in interest in the topic of corruption, resulting in a rising demand for suitable teaching materials. This edited collection brings together two different approaches to the study of corruption - the first represented by a large, practically-oriented literature devoted to identifying the causes of corruption, assessing its incidence and working out how to bring it under control; the second by a smaller collection of critical literature in political theory and intellectual history that addresses conceptual and historical issues concerned with how corruption should be, and how it has been, understood - and uses the second to reflect on the first. This collection will be of interest to post-graduate students in political science, law, sociology, public policy and development studies, to senior public servants, and to professionals working in multilateral agencies, NGOs and the media.